UNSUR-UNSUR BUDAYA DALAM AMTSÂL ’ARABIYYAH (PERIBAHASA ARAB) - Mahwiyah, Siti (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2014)
This article analyze the cultural values in proverb of Arabic (amtsal). The analysis of Amtsal are from the history of ancient Arabian. The results shows that Amtsal reflect cultural values such as; culture, life style, mindset, geography position, and economic activity of ancient Arabian. DOI: 10.15408/a.v1i2.1142